2022
DOI: 10.21203/rs.3.rs-2265012/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anaemia, iron deficiency and inflammation prevalence in children in the Mount Cameroon area and the contribution of inflammatory cytokines on haemoglobin and ferritin concentrations: a cross sectional study

Abstract: Background Iron deficiency (ID) and anaemia of inflammation (AI) coexist where infections and nutritional deficiencies are common. The aim of this study was to determine burden of ID, anaemia, inflammation and AI in children in malaria endemic Limbe, Mount Cameroon as well as decipher the contribution of some inflammatory cytokines on the concentration of haemoglobin and ferritin. Methods A total of 520 children aged ≤ 15 years old from the Limbe Health District (LHD) were randomly selected and examined in a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…From these results, it can be concluded that there was no difference in iron intake after nutrition education between the intervention group with the speech method and TGT with the control group with the speech method to Adolescent Girls at Public High School 1 Tanjung Redeb. The Sama et al ( 2023) study in Cameroon found insufficient meat consumption in a week, plantains (which are rich in iron) and fruits, (which facilitate iron absorption) were reported as risk factors for anemia, and Iron deficiency has been established as the leading cause of anemia (20). A previous study in Brazil suggested that consumption of dairy products, meat, and dietary diversity was associated with a low prevalence of anemia in adolescent girls (21).…”
Section: Nutrition Education On Fe Intake Of Adolescent Girlsmentioning
confidence: 99%
“…From these results, it can be concluded that there was no difference in iron intake after nutrition education between the intervention group with the speech method and TGT with the control group with the speech method to Adolescent Girls at Public High School 1 Tanjung Redeb. The Sama et al ( 2023) study in Cameroon found insufficient meat consumption in a week, plantains (which are rich in iron) and fruits, (which facilitate iron absorption) were reported as risk factors for anemia, and Iron deficiency has been established as the leading cause of anemia (20). A previous study in Brazil suggested that consumption of dairy products, meat, and dietary diversity was associated with a low prevalence of anemia in adolescent girls (21).…”
Section: Nutrition Education On Fe Intake Of Adolescent Girlsmentioning
confidence: 99%